Postoperative Glottal Function and Voice‐Related QOL after Type1 and Type2 Cordectomy against Laryngeal Leukoplakia. (2nd September 2014) - Kono, Takeyuki; Saito, Koichiro; Yabe, Haruna; Uno, Kosuke; Ogawa, Kaoru
Abstract : Objectives: Recent progress in phonomicrosurgical technique and equipment enabled one to precisely differentiate the subepithelial (type1) and subligamental (type2) cordectomy concept as needed. The purpose of this study was to compare postoperative glottal function and voice‐related quality of life (QOL) between these 2 surgical concepts against laryngeal leukoplakia. Methods: From January 2007 to August 2013, 42 consecutive laryngeal leukoplakia patients had excisional biopsies using type1 procedures. Of these, cancer patients (n = 10) had additional type2 laser surgeries. Furthermore, some severe dysplasia/carcinoma in situ patients (n = 11) preferred additional type2 surgery aiming at relatively safe surgical margins. Sequential pre‐ and postoperative measurements of Grade, Roughness, Breathiness, Asthenia, Strain (GRBAS) scale and evaluations of laryngeal videostroboscopic images were performed. Acoustic measurements and voice‐related QOLs (VHI and V‐RQOL) were examined at the patients' last visits. All data were compared between type1 and type2 groups. Results: Vocal quality was well‐preserved in type1 group after surgery. Although immediate postoperative deterioration of GRBAS score was observed in type2 group, vocal recovery was obtained in 6 months to present no significant difference compared with type1 group. Impaired glottal closure and pliability were observed in both groups after surgery. While videostroboscopic findings of type1 group recovered to normal in 3 months, impaired glottal findings remained for 1 year in half of the type2 patients. Moreover, voice‐related QOLs were significantly better in type1 group. Conclusions: Our study proved that advanced phonomicrosurgical technique and equipment could offer a well‐preserved vocal quality even in the type2 group. However, subjective voice‐related QOLs were better in the type1 group with superior videostroboscopic findings.